Autologous Osteoperiosteal Transplantation for the Treatment of Large Cystic Talar Osteochondral Lesions. Issue 1 (15th November 2022) - Guo, Hao; Chen, Zhuhong; Wei, Yuxuan; Chen, Botao; Sun, Nian; Liu, Yijun; Zeng, Canjun
Abstract : Objective: The effectiveness of autologous osteoperiosteal transplantation (AOPT) for the treatment of large cystic talar osteochondral lesions (OCLs) should be further evaluated, and the postoperative cartilage coverage is questionable. The purpose of this retrospective observational study was to investigate the clinical outcomes of AOPT for the treatment of large cystic talar OCLs and to report second‐look arthroscopic results. Methods: From June 1, 2017, to June 1, 2021, all talar OCLs at our center were reviewed. Painful cystic lesions treated with AOPT were included in the study. The American Orthopaedic Foot and Ankle Society (AOFAS; 0–100 points) ankle‐hindfoot score, Foot Function Index (FFI; 0–100 points), visual analog scale (VAS; 0–10 points) score, and Tegner score (0–10 points) were used to describe pain and functional outcomes. Furthermore, complications, patient‐reported satisfaction degrees, imaging results (including computed tomography and magnetic resonance), and second‐look arthroscopic evaluation data were also collected for analysis. Results: A total of 29 cases were eligible for the study, and 26 responded to the latest follow‐up request, with a mean follow‐up duration of 30.2 (range, 12–57) months. The AOFAS score improved from 69.2 ± 10.9 preoperatively to 80.9 ± 10.0 at the latest follow‐up ( p = 0.000). The FFI score improved from 30.4 ± 18.4 preoperatively to 16.3 ± 14.0 at the latest follow‐up ( p = 0.000). The VAS pain score improved from 4.0 ± 2.1 preoperatively to 2.5 ± 2.0 at the latest follow‐up ( p = 0.001). No donor site morbidity was found. The mean postoperative MOCART score was 57.7 ± 9.5. Second‐look arthroscopy showed a fibrillated cartilage‐like surface at the lesion site in most cases, while two cases exhibited a nearly normal surface. Conclusion: The transplantation of osteoperiosteal cylinder autografts taken from the iliac crest for the treatment of large cystic talar OCLs yielded acceptable clinical results. Good integration of the bony part was observed, but cartilage regeneration remained uncertain. Abstract : Large cystic talar osteochondral lesions are intractable clinical problems. The transplantation of osteoperiosteal cylinder autografts taken from the iliac crest for the treatment of large cystic lesions yielded acceptable pain and functional results. Excellent integration of the bony part was observed, but cartilage regeneration remained uncertain.